Patterns of acid reflux in complicated oesophagitis. Issue 11 (November 1987) - Robertson, D; Aldersley, M; Shepherd, H; Smith, C L
Abstract : Oesophageal manometry and 24 hour ambulatory pH recordings from the distal oesophagus were carried out in 25 patients with complications of oesophagitis (stricture, Barrett's oesophagus or oesophageal ulcer) and compared with 25 patients with uncomplicated oesophagitis. Acid reflux was more severe in the complicated group with 26.2% of time below pH 4 compared with 11.3% in uncomplicated patients (p less than 0.01). This difference was most marked at night, when complicated patients had long periods of acid reflux with 35.6% time less than pH 4 compared with 5.2% uncomplicated (p less than 0.001). The mean duration of nocturnal acid reflux was 15.4 minutes (2.1 minutes uncomplicated, p less than 0.001). Oesophageal motility was markedly abnormal in all groups, but with no demonstrable differences in lower oesophageal sphincter pressure or peristalsis between the groups. Patients with complications of oesophagitis have different patterns of acid reflux from uncomplicated patients, with prolonged nocturnal bathing of the oesophageal mucosa, which may be the cause of stricture formation, metaplasia, or ulceration.